Use of Simulation to Test Systems and Prepare Staff for a New Hospital Transition. Issue 3 (September 2018) - Adler, Mark D.; Mobley, Bonnie L.; Eppich, Walter J.; Lappe, Molly; Green, Michaeleen; Mangold, Karen
Abstract : Objective: To describe the development and key outcomes arising from the use of simulation as a method to test systems and prepare staff for a transition to a new hospital. Methods: We describe a simulation program developed by key parties with the goal of reducing latent safety threats present at the opening of a new hospital and to train staff in new workflows. Issues identified were collected and reported to leadership. Outcomes included the number of learners reached, issues identified (grouped by theme), and results of a postmove survey of hospital-based staff. Results: Approximately 258 hours of simulation were conducted, impacting 514 participants. We conducted 64 hours of system testing and 196 hours of training during the main orientation process. Approximately 641 unique issues were identified (175 equipment, 136 code alarm, 174 barriers to care, and 156 incorrect signage). In a hospital-wide survey, 38% reported simulation as part of their training (39% of nurses and 23% of physicians). 43% of survey respondents reported multidisciplinary simulations; 55% of simulation attendees felt that the simulation was helpful and eased their transition to the new hospital. Conclusions: Systems testing and education using simulation can play a meaningful role in new facility training. Key lessons included early planning, allocation of resources to the effort, flexibility to adapt to changes, and planned integration with other training activities. A formal a priori plan to address issues identified during the process is necessary. Abstract : Supplemental digital content is available in the text.